2009
DOI: 10.1370/afm.904
|View full text |Cite
|
Sign up to set email alerts
|

Having a Personal Health Care Provider and Receipt of Colorectal Cancer Testing

Abstract: PURPOSE We wanted to assess the relationship between having a personal health care provider and receiving colorectal cancer testing.METHODS Self-reported data were obtained from the United States 2004 Behavioral Risk Factor Surveillance System. Men and women aged 50 years and older were included, and associations of having a personal health care provider, age, sex, race/ethnicity, education, income, and health insurance status with colorectal cancer testing were examined. Multiple logistic regression was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
(28 reference statements)
5
16
0
Order By: Relevance
“…We employed conditional logistic regression analyses 19,20 to model within-individual changes in preventive care and health behaviors associated with within-individual changes in health insurance status. One set of models was unadjusted, while a second set was adjusted for factors that may both change year to year and influence preventive care and health behaviors: income level, 21,22 employment status, 23 total health care expenditures, 24 the number of office visits to health care providers, 25,26 the number of medication prescriptions, 24 availability of a usual source of care, [27][28][29][30] and health status. 31 An advantage of conditional logistic regression in this context is that it simultaneously models individual increases or decreases in preventive care and health behaviors associated with individual gain or loss of insurance, providing a more robust estimate of the effects of insurance change (approximately doubling the sample size of those changing insurance status) and yielding an average of the effects of insurance gain and loss.…”
mentioning
confidence: 99%
“…We employed conditional logistic regression analyses 19,20 to model within-individual changes in preventive care and health behaviors associated with within-individual changes in health insurance status. One set of models was unadjusted, while a second set was adjusted for factors that may both change year to year and influence preventive care and health behaviors: income level, 21,22 employment status, 23 total health care expenditures, 24 the number of office visits to health care providers, 25,26 the number of medication prescriptions, 24 availability of a usual source of care, [27][28][29][30] and health status. 31 An advantage of conditional logistic regression in this context is that it simultaneously models individual increases or decreases in preventive care and health behaviors associated with individual gain or loss of insurance, providing a more robust estimate of the effects of insurance change (approximately doubling the sample size of those changing insurance status) and yielding an average of the effects of insurance gain and loss.…”
mentioning
confidence: 99%
“…However, similar screening rates were achieved with significantly fewer reminder letters in intervention practices where PCPs reviewed their overdue patients, and intervention PCPs reported spending less time during clinic hours on cancer screening tasks. Studies have shown that involvement of a PCP [23][24][25][26][27][28] and non-visit-based reminder systems 10,[12][13][14][15][16][17]36,37 can increase rates of preventive cancer screening. The current study demonstrates that an automated reminder IT application without physician input led to similar screening rates for patients who seemed to be overdue for up to 3 widely recommended cancers: breast, cervical, and colorectal.…”
Section: Discussionmentioning
confidence: 99%
“…We implemented this application as part of a practice-randomized trial that compared involving PCPs in the screening process to customize outreach with a fully automated outreach process. Although higher cancer screening rates are associated with having a PCP 23,24 and the PCP recommending screening, [25][26][27][28] the role of the PCP in non-visit-based outreach efforts is unclear. We hypothesized that having PCPs determine whether contact was needed-and, if needed, how best to provide it-would lead to an increase in cancer screening rates.…”
mentioning
confidence: 99%
“…16 Data obtained in Catalonia indicated that 88.9% of individuals would agree to participate in a colorectal cancer screening programme if their primary care professional suggested it; 17 this figure, however, is far from the actual participation rates. In Catalonia, public primary care is organised through primary care centres that each cover a specific population area.…”
Section: Introductionmentioning
confidence: 99%